Stress- and Growth Phase-Associated Proteins of Clostridium acetobutylicum - Terracciano, Joseph S. (1988)
The response of Clostridium acetobutylicum ATCC 4259 to the stresses produced by a temperature upshift from 28°C to 45°C and by exposure of the organisms to 0.1% n-butanol or to air was examined by analysis of pulse-labeled proteins. The stress response was the induction of the synthesis of a number of proteins, some of which were elicited by the three forms of stress. Eleven heat shock proteins were identified by two-dimensional electrophoresis, as were two proteins whose synthesis was heat sensitive. In the absence of applied stress, the synthesis of four proteins was found to be associated with the growth phase in batch culture; three of these proteins had a higher rate of de novo synthesis when the cells entered the solvent production phase. One of the stress-induced proteins, hsp74, was partially purified an found to be immunologically related to Escherichia coli heat shock protein Dnak. The similarities of the proteins induced at the onset of solventogenesis and by stress suggest a relationship between the two processes.